Art since 1980 : charting the contemporary - Kalb, Peter R. (London : Laurence King Publishing, 2013)
"Charts the story of art in contemporary global culture while holding up a mirror to our society. With over 300 pictures of painting, photography, sculpture, installation, and performance and video art, we are led on an illuminating journey via the individuals and communities who have shaped art internationally"--Book jacket.
Includes bibliographical references (pages 320-325) and index.
Keywords: Art, Modern -- 20th century; Art, Modern -- 21st century